Revising the paradigm for jail diversion for people with mental and substance use disorders: Intercept 0. (16th October 2017) - Abreu, Dan; Parker, Travis W.; Noether, Chanson D.; Steadman, Henry J.; Case, Brian
Abstract : A conceptual model for community‐based strategic planning to address the criminalization of adults with mental and substance use disorders, the Sequential Intercept Model has provided jurisdictions with a framework that overcomes traditional boundaries between the agencies within the criminal justice and behavioral health systems. This article presents a new paradigm, Intercept 0, for expanding the utility of the Sequential Intercept Model at the front end of the criminal justice system. Intercept 0 encompasses the early intervention points for people with mental and substance use disorders before they are placed under arrest by law enforcement. The addition of Intercept 0 creates a conceptual space that enables stakeholders from the mental health, substance use, and criminal justice systems to consider the full spectrum of real‐world interactions experienced by people with mental and substance use disorders with regard to their trajectories, or lack thereof, through the criminal justice system.